2021
DOI: 10.3102/0013189x211023514
|View full text |Cite
|
Sign up to set email alerts
|

Do Peers Affect Undergraduates’ Decisions to Switch Majors?

Abstract: In this study, dormitory room and social group assignment data from a college are used to investigate peer effects on college students’ decisions to switch majors. Results reveal strong evidence of such peer effects at both the room and the social group level. Most notably, at the room level, the dense concentration of same-major roommates deters students from switching majors; having one or two same-major roommates has no significant effect on major switching, indicating strong nonlinearity of peer effects at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The second theme illustrated how students came to perceive their initial major as inadequate for meeting their needs and fostering success, adding nuance to understandings of factors that spark interest in changing majors. While career goals, GPA requirements, and other previously documented factors clearly played a role (Pu et al 2021 ; Meyer et al, 2022 ), students’ meaning making about the support and resources available through various majors was likewise influential. Schlossberg ( 1981 ) articulated the importance of support for successfully navigating a transition once it is underway; this finding illustrates the ways support (or a lack thereof) can also spark a transition.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The second theme illustrated how students came to perceive their initial major as inadequate for meeting their needs and fostering success, adding nuance to understandings of factors that spark interest in changing majors. While career goals, GPA requirements, and other previously documented factors clearly played a role (Pu et al 2021 ; Meyer et al, 2022 ), students’ meaning making about the support and resources available through various majors was likewise influential. Schlossberg ( 1981 ) articulated the importance of support for successfully navigating a transition once it is underway; this finding illustrates the ways support (or a lack thereof) can also spark a transition.…”
Section: Discussionmentioning
confidence: 92%
“…Studies examining the topic of changing majors after a student has declared an initial major are primarily quantitative, documenting the frequency of switching fields of study or factors that prompt students to declare a new major (Drysdale et al, 2015 ; Pu et al, 2021 ; Riegle-Crumb et al, 2016 ). Analyzing data from a panel study of German students, Meyer et al ( 2022 ) found that factors like prior academic achievement, career goals, and social expectations impacted whether students changed majors.…”
Section: Choosing and Changing Majorsmentioning
confidence: 99%
“…We might argue that dormitory relationships have strong links with individuals' sense of belonging to the school. Prior research has also revealed that dormitory roommates have a strong influence on individual decision making and that the density of roommates with the same major discourages students from changing majors [72]. In addition, as time progressed, the proportion of classmates among their peers increased and the proportion of dorm roommates among their peers declined, which indicates that the classroom becomes an important place for peer formation and influence.…”
Section: Main Findingsmentioning
confidence: 99%
“…The selection of the most appropriate academic major is a crucial aspect of this decision, directly influencing individuals' future career plans. Consequently, major selection and persistence have been subjects of extensive research over the years (Morgan et al, 2013; Pu et al, 2021; Shapiro & Sax, 2011; Trice et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, major selection and persistence have been subjects of extensive research over the years (Morgan et al, 2013;Pu et al, 2021;Shapiro & Sax, 2011;Trice et al, 1989).…”
Section: Introductionmentioning
confidence: 99%